Քրդերի ինքնավարության հիմնահարցը ժամանակակից Իրաքում - Մհոյան, Շաքրո («Զանգակ - 97»)
Complicated process of self-determination of Kurds in Iraq is one of the most important modern issues in the Middle East. There are two sets of aspects that could determine the fate of Kurdish autonomy in Iraq. Negative set consists of partitioning of Kurdistan and active anti-Kurdish policy of neighboring countries, radical Islam with its clear stance against autonomy, different approach of Iraqi political forces towards Kurdish problems and others.
Keywords: Պատմություն; Ազգագրություն